Vitamin D and Psoriasis. (8th October 2014) - Lowe, Karen E.; Norman, Anthony W.
Abstract : Skin can serve as the source of vitamin D when exposed to sunlight so that cutaneous 7-dehydrocholesterol can be converted to the vitamin. Skin is also a target organ for the hormone form of vitamin D: 1, 25-(OH)2 D3 . Both skin keratinocytes grown in tissue culture and samples of human skin have the nuclear receptor for 1, 25(OH)2 D3 . New results suggest that this hormone or its analogs may be effective in treating some forms of psoriasis.